Pengaruh Penambahan Pasir Terhadap Daya Dukung Subgrade Jalan - Yudha Fardyansah; Nurly Gofar (Department of Civil Engineering and Planning, Faculty of Engineering, Sriwijaya University, 2020)
The performance of flexible pavement is highly influenced by the quality of subgrade material. In Palembang, the foundation soil is usually consisted of clay which is sensitive to change in water content caused by rainfall as well as inundation. This paper presents results of laboratory study on the effect of adding sand to clay to be used as subgrade material for urban roads. California Bearing Ratio (CBR) values were used as indication of strength improvement of the subgrade in unsoaked and soaked conditions. The suitability of the stabilized soil for use as subgrade of pavement construction in response to normal and inundated conditions was further assessed through field verification using Dynamic Cone Penetrometer. Results of both laboratory and field studies indicated that addition of 21% sand by dry weight give the most improvement in terms of CBR value. In this case, the CBR unsoaked increased from 8% to 18% while the CBR soaked increased from less than 3% to 8%. Field verification showed that the CBR of compacted natural soil decreased from 8% to 2% after rainfall while the CBR of the sand stabilized soil decreased from 17% to 8%. Thus the sand stabilized clay is expected to perform adequately even after subjected to rainfall and inundation.